A New Functional Composite for Photovoltaic and Sensor Applications. (20th January 2021) - Ghosh, Puja; Roy, Anurag; Mukhopadhyay, Soumita; Narjinary, Mousumi; Sundaram, Senthilarasu; Sen, Shrabanee; Devi, Parukuttyamma Sujatha
Abstract: As a preliminary drive to eventually develop dye‐sensitized solar cell (DSSC)‐powered gas sensors, many oxide‐based systems have been explored to fabricate sensors that can show response at room temperature for any analyte gas. As an outcome of recent work in this endeavor, a composite nanorod of anatase TiO2 with Na0.23 TiO2 is found to exhibit both photovoltaic performance and gas sensing at room temperature as demonstrated here. An interesting morphology change along with a phase change from nanoparticle to nanorod is observed during the hydrothermal synthesis of anatase TiO2 nanoparticles with sodium hydroxide under a highly basic condition. In order to understand the effect of the minor phase Na0.23 TiO2 on the inherent properties of anatase TiO2, the application of nanorod composite in two unique potential application areas, DSSC and acetone sensings is investigated. The composite material exhibits an enhanced efficiency of 7.85% for a DSSC. Surprisingly, a resistive sensor fabricated with the synthesized composite material exhibits room temperature p‐type sensing behavior toward different concentrations of acetone (10, 5, 3, 2, and 1 ppm) with high selectivity. Abstract : An innovative composite material is formed during the hydrothermal synthesis of anatase TiO2 nanoparticles with sodium hydroxide under a highly basic condition. To understand the effect of the minor phase Na0.23 TiO2 on the inherent properties of anatase TiO2, the application of nanorod composite in two unique potential application areas, dye‐sensitized solar cells and acetone sensing, is investigated.